Suburbanization within the city? Exploring suburban lifestyles in the inner-city of Leipzig (Germany) - Koumparelou, Artemis; Feiler, Andreas; Kühn, Linda; Hübscher, Marcus (ERDKUNDE, 2023)
The long-prevailing image of a clear delimitation between core city and suburbs has been increasingly questioned in research. New qualitative approaches are necessary to describe the urban-suburban relationship based on a sociocultural heterogenization of suburbs and the spread of suburban lifestyles into inner cities. The concept of inner-city suburbanization is one approach to define spaces as urban or suburban regardless of geographical location. Drawing upon this concept, the present paper explores suburban lifestyles in the inner-city area of Leipzig and their role in the socio-spatial urban transformation. For this purpose, we identify and map owner-occupied middle-class family housing estates in central urban locations. Using qualitative individual and focus group interviews with the residents, complemented by site observation, we explore to what extent these single-family houses resemble traditional suburbs in terms of morphology and social structure in four different case studies. All of the cases show how suburban qualities, such as homeownership and socio-economical homogeneity, go hand in hand with the benefits of their urban locations. This hybrid character reflects the dissolution of the classical place-specific distinctions between urban and suburban environments and patterns. Simultaneously, dynamics of upgrading and social exclusion from housing unfold in the residential areas, where middle-class family housing estates emerge. Thus, we raise the question of the interrelation between inner-city suburbanization processes and gentrification trends in Leipzig.